Moderate physical activity during late pregnancy enhances gut microbial network stability in pregnant women - Tye, Kian Deng; Ran, XiaoXia; Liu, XiaoYi (Frontiers in Microbiology, 2025)
AimThis study aimed to investigate the impact of moderate physical activity during late pregnancy on the overall structure and stability of the maternal gut microbiota, with particular emphasis on microbial network interactions and their potential implications for mucosal immune resilience.MethodsA prospective cohort study was initiated at 32 weeks of gestation, during which physical activity was assessed, and fecal samples were subsequently collected at full-term admission for delivery. Fecal samples were collected and analyzed using 16S rDNA sequencing, and daily physical activity levels were recorded. Participants were categorized into two groups based on the duration of moderate-intensity physical activity: T1 (≥30 min/day, 18 women) and T2 (<30 min/day, 5 women). Bioinformatics analyses were used to compare gut microbiota composition, diversity, and network interactions between the groups, and to assess correlations between microbial abundance and physical activity levels.ResultsFirmicutes, Bacteroidetes, Actinomycetes, and Proteobacteria were the dominant phyla in both groups. Alpha diversity and principal coordinate analysis (PCoA) showed no significant differences in overall diversity. However, LEfSe analysis revealed an enrichment of Christensenellaceae and Prevotella stercorea in the T2 group. The gut microbial network in the T1 group was more complex and stable, with predominantly positive microbial correlations. Spearman analysis indicated significant associations between physical activity levels and specific gut microbes: sedentary behavior correlated negatively with Romboutsia (p = 0.033, R = −0.445) and was positively correlated with Senegalimassilia (p = 0.043, R = 0.443), light-intensity activity correlated negatively with Phascolarctobacterium (p = 0.015, R = −0.500), and moderate-intensity activity correlated positively with Parasutterella (p = 0.040, R = 0.432).ConclusionModerate physical activity during late pregnancy promotes a more stable and functionally interactive gut microbiota network. Such microbial resilience may strengthen mucosal immune regulation and reduce infection susceptibility during gestation. These findings highlight the potential of physical activity as a non-pharmacological strategy to modulate the maternal gut microbiome for improved host defense and health outcomes.